Students’ Perceptions of English Songs for Listening Comprehension - Insani, Tiara Salsabila (Jurnal Indonesia Sosial Sains, 2026)
One of the important skills that must be obtained in English language learning is listening comprehension. However, many students experience difficulties in understanding spoken English. This study investigates students' perceptions toward the use of English songs in improving listening comprehension. This study investigates EFL students’ perceptions of the use of English songs in improving listening comprehension. Employing a quantitative descriptive design, the study involved 32 English Department students who had completed a Survival Listening/Speaking course at a private university in Indonesia. Data were collected through a closed-ended questionnaire consisting of 25 items distributed across five indicators: motivation, vocabulary development, pronunciation awareness, listening comprehension, and learning interest. The questionnaire used a five-point Likert scale ranging from strongly disagree to strongly agree and was administered online. The data were analyzed using descriptive statistics, including frequencies, percentages, and mean scores. The findings reveal that students held positive perceptions toward the use of English songs in listening activities, particularly in terms of increasing motivation and enhancing vocabulary acquisition. English songs were also perceived as helpful in improving pronunciation awareness and overall listening comprehension, while creating a more enjoyable and less stressful learning atmosphere. These results suggest that integrating English songs into listening instruction can be an effective pedagogical strategy for EFL classrooms. The study provides practical implications for English teachers in designing engaging listening activities and recommends further research using experimental designs to examine the effectiveness of English songs on listening achievement.